Peningkatan Kemampuan Kognitif Siswa melalui Problem Based Learning dengan Evaluasi Berbasis Physics Playing Cards - Arin wildani; Agus Budiyono; Mohammad Lutfiadi (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study is to describe the increase in students' cognitive abilities as an effect of providing problem based learning treatment based on the evaluation of Physics Playing Cards. The method used in the implementation of this research uses a quasi-experimental method, where there is one class as the experimental class and another class as the control class. This study used two sample classes at the State Senior High School (SMAN) 4 Pamekasan which were taken randomly. This research instrument uses a cognitive ability test on wave material. Research data were taken before and after learning. Data were analyzed using N-gain to find out the increase in students' cognitive abilities. The results showed that there was a high increase in students' cognitive abilities in the experimental class and a moderate increase in students' cognitive abilities in the control class. This research can be concluded that the use of evaluation based on Physics Playing Cards in the problem based learning model has increased higher than the problem based learning model alone.